Clinical application of SNP array analysis in first‐trimester pregnancy loss: a prospective study. Issue 6 (22nd December 2016) - Wang, Y.; Cheng, Q.; Meng, L.; Luo, C.; Hu, H.; Zhang, J.; Cheng, J.; Xu, T.; Jiang, T.; Liang, D.; Hu, P.; Xu, Z.
Abstract : Chromosomal microarray analysis (CMA) has been used routinely in pediatric and prenatal genetic diagnosis in clinical practice, but it has rarely been applied to miscarriage analysis. In this study, we conducted a prospective study to evaluate the feasibility of CMA for genetic diagnosis of first‐trimester miscarriage specimens. We successfully analyzed 551 fresh miscarriage specimens using single‐nucleotide polymorphism (SNP) array. Among the specimens, 2.9% (16/551) had significant maternal cell contamination and were excluded from the study. Clinically significant chromosomal abnormalities were identified in 295 (55.1%) cases, including 214 (40%) with aneuploidy, 40 (7.5%) with polyploidy, 19 (3.6%) with partial aneuploidy, 12 (2.2%) with pathogenic microdeletion/microduplication, and 10 (1.9%) with uniparental isodisomy (isoUPD). Variants of uncertain significance were obtained in 15 cases (2.8%). Notably, isoUPD involving a single chromosome (chromosome 22) and two recurrent copy number variations, 22q11.2 microdeletion and 7q11.23 microdeletion, were identified as probably to be associated with miscarriage. The frequency and distribution of genetic aberrations in the spontaneous abortion group was not significantly different from those in the recurrent miscarriage group. Our study suggests SNP array is a reliable, robust, and high‐resolution technology for genetic diagnosis of miscarriage in clinical practice. Abstract :